2020
DOI: 10.1167/iovs.61.10.23
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Through the Erythropoietin Receptor Affects Angiogenesis in Retinovascular Disease

Abstract: PURPOSE. Exogenous erythropoietin (EPO) is being considered for tissue protection and angiogenesis in retinal vascular diseases. However, studies are limited by insufficient tools to address signaling effects through the EPO receptor (EPOR). We used a humanized mouse model of hypoactive EPOR signaling to test the hypothesis that EPOR signaling supports angiogenesis in retinovascular diseases. METHODS. Humanized Knockin EPOR mice (hWtEPOR) with hypoactive EPOR signaling were compared to littermate wild-type mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…EPOR is present not only in hematopoietic cells but also in non-hematopoietic cells such as neurons [19], endothelial cells [20], skeletal muscle cells [45] and in various tumors such as breast cancer [46] and head and neck cancer [47]. EPOR expression was also detected in lung cancer cell lines such as H838 [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPOR is present not only in hematopoietic cells but also in non-hematopoietic cells such as neurons [19], endothelial cells [20], skeletal muscle cells [45] and in various tumors such as breast cancer [46] and head and neck cancer [47]. EPOR expression was also detected in lung cancer cell lines such as H838 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of JAK2 results in the activation of speci c downstream effectors, such as STAT1, STAT3, or STAT5 [13], the signal transducer and activator of transcription 5 (STAT5) usually refers to STAT5A and STAT5B proteins [14], thus activates phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), mitogen-activated protein kinase (MAPK) and extracellular signalregulated kinase 1/2 (ERK1/2) [15,16]. EPOR was originally discovered and described in erythroid progenitor cells, but it is also present in non-hematopoietic cells (tissues, organs) such as adipose tissues [17], bone progenitor cells [18], neurons [19], endothelial cells [20] and intestinal tract [21]. It is also widely present in various cancer cells and tumor tissues, such as head and neck squamous cell carcinoma [22], diffuse large B-cell lymphoma [23], rhabdomyosarcoma [24], breast cancer [25], hepatocellular carcinoma…”
Section: Introductionmentioning
confidence: 99%
“…endothelial cells [20], skeletal muscle cells [45] and in various tumors such as breast cancer [46] and head and neck cancer [47]. EPOR expression was also detected in lung cancer cell lines such as H838 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of JAK2 results in the activation of speci c downstream effectors, such as STAT1, STAT3, or STAT5 [13], the signal transducer and activator of transcription 5 (STAT5) usually refers to STAT5A and STAT5B proteins [14], thus activates phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), mitogen-activated protein kinase (MAPK) and extracellular signalregulated kinase 1/2 (ERK1/2) [15,16]. EPOR was originally discovered and described in erythroid progenitor cells, but it is also present in non-hematopoietic cells (tissues, organs) such as adipose tissues [17], bone progenitor cells [18], neurons [19], endothelial cells [20] and intestinal tract [21]. It is also widely present in various cancer cells and tumor tissues, such as head and neck squamous cell carcinoma [22], diffuse large B-cell lymphoma [23], rhabdomyosarcoma [24], breast cancer [25], hepatocellular carcinoma [26] and laryngeal malignancy [27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PEDF overexpression has also been shown to attenuate VEGF and β-catenin expression ( Park et al, 2011 ). Moreover, EPO signaling has reduced angiogenesis and vascularization following OIR in mice ( Bretz et al, 2020 ). The expression of NPY and substance P has been observed to decrease in the OIR mouse and they do not appear to play any role in neovascularization, which was further validated in the NPY KO mice, where it was found that NPY does, in fact, not take part in vascularization ( Schmid et al, 2012 ).…”
Section: Metabolic Retinal Diseases: Pathology and Neuropeptidesmentioning
confidence: 99%